CO2 DIODE LASER HEMORRHOIDECTOMY: CLINICAL EXPERIENCE WITH 150 PATIENTS (Iraqi Journal of Medical Sciences, 2018)
Background: Hemorrhoids are the most common benign anorectal conditions. About half of population are affected by hemorrhoids during their life time. Conventional surgical hemorrhoidectomy, which was the standard treatment for many decades are associated with remarkable and intolerable pain that may last up to 3 to 6 weeks, which makes more patients reluctant to surgery. Laser hemorrhoidectomy is relatively new promising modality with less postoperative pain and less complications with fast wound healing and early return to work.Objective: To assess the validity, feasibility and the outcomes of using the CO2 diode laser for treatment of symptomatic hemorrhoids.Methods: A prospective study conducted for the period from September 2013 to April 2015, included 150 patients (135 male and 15 female), with symptomatic first, second and third degree piles with age ranged from 24 to 83 years (mean 48.7 year) submitted to CO2 diode laser hemorrhoidectomy with either the coagulation mode or cutting mode of 30 Watt diode laser surgical machine. The procedures were done under local anesthesia as a day case surgery by single surgeon. Results: The results showed that the operative time ranges from 15 to 30 minutes (mean 23.5 minutes). Postoperative pain scores by visual analog scale (VAS) in the first, second and third postoperative days were 2.9, 2.1, 1.8 respectively. The pain decreased rapidly after the first week and reached to zero after 14 days postoperatively. The complications rate recorded in this work was 7.3%. All these complications were mild and can be dealt with conservatively; redo surgery was not required in any case. All patients were discharged 2 to 4 hours postoperatively and were followed for 3 to 6 months.Conclusion: Hemorrhoidectomy by CO2 diode laser is effective, and very quick outpatient procedure with very mild postoperative pain and low or negligible rate of complications. It associated with rapid healing and fast recovery that most patient can return to normal daily activity within 2 to 5 days. These results are considered a big advantage upon conventional hemorrhoidectomy.Keywords: Hemorrhoids, laser hemorrhoidectomy, CO2 diode laserCitation: Noori IF. CO2 Diode Laser hemorrhoidectomy: clinical experience with 150 patients. Iraqi JMS. 2017; Vol. 15(4). 411-419. doi: 10.22578/IJMS.15.4.12
Keywords: Hemorrhoids; laser hemorrhoidectomy; CO2 diode laser